Bibliometric Analysis on the Word Procrastination - Munandar, Zikri Bagas (Westscience Press, 2025)
This study aims to understand how research trends on procrastination have evolved over time. Using bibliometric methods, the authors analyzed 1,000 documents from Google Scholar that discussed this topic from 1973 to 2024. The results of the analysis show that the number of studies on procrastination has increased significantly in recent years, especially after 2010. Topics that often appear are related to stress, self-control, academic achievement, and other psychological and social factors. Data visualization with the help of VOSviewer software shows that procrastination is a complex topic and involves many fields of science. This study is expected to help academics and practitioners to better understand the direction of research developments on procrastination and develop more effective treatment strategies.